Peningkatan Sadar Hukum Siswa di Madrasah Aliyah Tholabuddin Masin mengenai Pengaruh Media Sosial terhadap Judi Online di Kalangan Pelajar melalui Sosialisasi Pencegahan Judi Online terhadap Pelajar - Lailatun Nafis; Bagas Heradhyaksa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In the Legislation of the Republic of Indonesia, online gambling has been strictly regulated and prohibited. However, it is unfortunate that this does not affect public awareness regarding the prohibition of online gambling games. To create a generation that has an awareness of the dangers of online gambling, it is necessary to provide the right material and direction for the community. through legal awareness raising activities regarding the influence of social media on online gambling among students as a first step in preventing online gambling for students, especially for students at Madrasah Aliyah Tholabuddin Masin. In this activity, the authors used the method of presentation and discussion related to the prevention and handling of online gambling entitled Smart Generation: Stop Online Gambling. The specific target of this activity is that Madrasah Aliyah Tholabuddin Masin students can be well educated about the meaning, legal basis and efforts to prevent and overcome online gambling cases. The main purpose of holding this activity is expected to be able to apply the values that show the spirit of state defense to the next generation of the nation in becoming a superior generation in the future. The increase in understanding and knowledge of students can be seen from the post test results which show that students are able to understand the material that has been presented in this community service.